Muslim Immigrants in Germany Challenge Integration - Ohser, Erickh (Edinost in dialog, 2025)
Turkish workers who emigrated from their country to Germany could reunify with their families; and now their descendants live there as German citizens. During turmoils and wars in The Middle East, Africa and Bosnia and Herzegovina many people fled their countries and immigrated to Germany as refugees and asylum seekers. Most of the refugees were Muslim and they all built their own communities, mosques and businesses as Turks had done before. They are Muslims; however, they have different cultures, languages, and denominations. They have had differences among themselves, moreover after decades of living in Germany their successful integration is still a question. We present a historical overview of the integration of Muslims in Germany, discuss the reasons for its failure and highlight the fears that non-Muslims and Muslims face in an increasingly Muslim society. We argue that in the future, society will have to face these fears, not to suppress them, but to take them seriously and find ways to allay them and thus ensure peaceful coexistence between people of different worldviews in a Western multicultural society.